The White Striping myopathy in different broiler strains and its influence on composition and meat quality Miopatia White Striping em diferentes linhagens de frangos de corte e suas consequências sobre a composição e a qualidade da carne - Lucca J.W.* (2019)
© 2019, Universidade Federal de Minas Gerais.The incidence of the White Striping (WS) myopathy in three male broiler strains and its consequences on the chemical composition and physical quality of the meat was evaluated. A completely randomized design (DIC) with three treatments (strains A, B and C) and five replicates of 300 breasts each were used to determine the incidence rates of the different degrees of WS myopathy (normal, moderate and severe) in each strain. For the chemical and physical variables, a 3 X 3 factorial scheme was used (three strains X three WS levels), with 15 replicates. The data were submitted to ANOVA and in cases of significant differences the Tukey test (P < 0.05) was used.The A strain chickens presented 84.81% of breasts classified as normal and 9.91% of breasts classified as moderate, respectively higher and lower values than in the other two strains. Breasts classified with severe WS myopathy were heavier and had higher percentages of lipids and moisture, and lower concentration of crude protein. However, the concentrations of total, soluble and insoluble collagen had interaction effects between lineage and WS level in the fillets, and therefore, the same behavior was not observed in the samples of the different strains.